Democratic biopolitics : popular sovereignty and the power of life - Prozorov, Sergei (Edinburgh scholarship online., 2019)
Contemporary studies of biopolitics assume that the rise of biopolitical governance entails the eclipse of democracy. The abstract egalitarianism of democratic government appears to be incompatible with the concrete, particularist and individualising operations of biopower. Sergei Prozorov challenges the assumption that the biopolitical governance means the end of democracy, arguing for a positive synthesis of biopolitics and democracy. He develops a vision of democratic biopolitics where diverse forms of life can coexist on the basis of their reciprocal recognition as free, equal and in common. He demonstrates how this vision can be realised and sustained by using examples of our lived experience --